MAPPING THE LEGAL LANDSCAPE OF LEGAL AWARENESS IN ARTIFICIAL INTELLIGENCE ADOPTION: BIBLIOMETRIC ANALYSIS AND SYSTEMATIC LITERATURE REVIEW - Kartiko, Nafis Dwi (Badan Pembinaan Hukum Nasional, 2026)
The integration of artificial intelligence raises complex legal consequences related to accountability and legal awareness. This study maps the intellectual landscape of legal awareness in AI adoption through bibliometric analysis and a Systematic Literature Review. The Bibliometric-Systematic Literature Review method integrates quantitative mapping with qualitative synthesis of 12 articles from the Scopus database. The results show exponential growth in publications after 2018, dominated by computer science perspectives rather than legal disciplines. The findings identify a gap between technological innovation and the development of legal doctrine, creating a normative vacuum. Legal awareness functions as a vital internal control mechanism prior to external regulatory enforcement. This study recommends an adaptive legal framework that emphasizes regulatory literacy and the human-in-the-loop principle. The research provides a foundation for the development of AI governance that is responsive to the dynamics of digital technology.